Aortic and bronchial perforation caused by a vascular clip 3 years after its placement. (9th September 2022) - Omori, Akiharu; Inuzuka, Ryo; Matsui, Hikoro; Hirata, Yasutaka
Abstract: Vascular clips are currently acknowledged as a safe and efficient tool for vessel ligation in every surgical field. Here, we describe a case of massive haemoptysis due to perforation of both the aorta and bronchus, caused by a titanium clip that was placed between them 3 years ago. The present case highlights the rare but life-threatening complications that clips can cause in the mediastinum, especially when placed between a fixed structure and a large blood vessel or respiratory tract. Abstract : Cushing first introduced the use of metal clips during surgical procedures >100 years ago [1].